Essays on strategic naivety and disclosure of verifiable information - Sheth, Jesal Dilip (2019)
The unravelling prediction of the disclosure theory relies on the idea that market forces lead firms (information senders) to voluntarily disclose information about the quality of their products provided the information disclosed is verifiable and the costs of disclosure are negligible. This theoretical prediction requires that consumers (information receivers) hold correct beliefs and, in equilibrium, treat all non-disclosed information with extreme scepticism. Previous research finds that receivers are insufficiently sceptical, i.e. are ‘strategically naïve’, about non-disclosed information, which leads to the failure of complete unravelling.